Efficient Charge Storage Capability of BiFeO3-Based Bi-Phase Nanocomposites. (4th February 2022) - Ali, Singay; Younis, Muhammad; Yaqub, Muhammad Atif; Ramay, Shahid M.; Atiq, Shahid
Abstract : Here, we report a facile synthesis of bi-phase nanocomposites of the form (1−x)BiFeO3 −xPbTiO3 for their efficient utilization in modern day energy storage gadgets. X-ray diffraction confirmed the distorted rhombohedral structure of pure BiFeO3 while PbTiO3 exhibited tetragonal structure and hence confirmed the formation of nanocomposites. Morphological analysis revealed the reduction in particle size, improvement in bulk density and decrease in porosity with the increase of PbTiO3 contents. A wide dispersion in dielectric response was explained on the basis of Maxwell-Wagner model. A significant improvement in dielectric behavior was observed when PbTiO3 was added in the composite. The contribution of grains and grain boundaries in the electrical response of these composites was witnessed through impedance analysis. The nature of charge transport mechanism was established using electric modulus spectroscopy. These kinds of nanocomposites are recommended for the improvement of data storage capacity of devices as compared with phase-pure compounds.